The Effect of Occupant Behavior on the Residential Visual Environment: A Case Study from Annaba, Algeria - Makhlouf Salma; Cheraitia Mohammed (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA)
The construction of comfortable, energy-efficient and health-friendly homes is more crucial than ever at a time when the health crisis is forcing us to reconsider our way of life. This article used a post-occupancy evaluation of the inhabited space in residential buildings at Oued El-Fourcha neighborhood in Annaba to assess user satisfaction with occupied buildings, examine the impact of daylighting and human behavior on the lighting ambience. The results of the study were processed by SPHINX Lexica software, focusing mainly on the qualitative aspects of daylighting in the inhabited space, taking into account occupant preferences. The study demonstrated an unfavorable level of internal illuminance, and that adequate lighting also needs to meet occupant requirements in order to make these windows usable, which must satisfy a number of socio-cultural, climatic and environmental factors.